Analysis of Dribbling, Passing, and Shooting Ability (1 Point, 2 Point, 3 Point) in the Mature Basketball Club Players Aged 16 Years - Indah Yustina P; Agus Sulastio; Alimandan Alimandan (CV. Rayyan Dwi Bharata, 2025)
This research aims to determine the Dribble, Passing and Shooting abilities (1 point, 2 points, 3 points) in the Mature Basketball Club Players in the 16 Year Age Category. This type of research is quantitative descriptive research, with test and measurement methods. The research population was athletes from The Mature Basketball Club, aged 16 years, totaling 20 athletes. The sample for this research was 20 athletes. Some of the test instruments carried out include dribble control tests, passing tests and shooting tests (free throw, under ring, three point). Based on the research results, it shows that the Dribble ability of The Mature Basketball Club athletes is in the